2020
DOI: 10.21203/rs.2.21930/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of metabolic syndrome among people living with HIV in the Gedeo-Zone, Southern-Ethiopia: an unmatched case-control study

Abstract: BackgroundMetabolic syndrome (MS) among people living with HIV (PLHIVs) is a global public health issue. However, there is no primary data about predictors of MS in the SSA and Ethiopia. Therefore, the aim of this study was to determine predictors of MS, among PLHIVs in the Gedeo-Zone,Southern-Ethiopia.MethodsUnmatched case-control study approach, among PLHIVs who served at randomly chosen two hospitals and health centers in the zone, in between (December 29th-2017 and January 22nd-2019) was done. WHO-steps to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(112 reference statements)
1
1
0
Order By: Relevance
“…Previous studies from Nigeria that has compared PLWHIV on ART and ART naive found a higher prevalence of MetS among the former (Muhammad et al, 2017;Muhammad et al, 2013;Ojong et al, 2022). Also, studies from other African countries (Bune et al, 2020 andOsoti et al, 2018) reported similar trend. However, among the PWoH in this study who are apparently healthy individuals, the prevalence of MetS was found to be 14.5%, which was higher than other studies (Raimi et al, 2018;Muazu et al, 2019;Ojong et al, 2022), which reported prevalence of 4.9%, 8.8% and 2.7%, respectively, though Adeyemi et al, 2017 andAmaewhule et al (2021) reported a very high prevalence of 36.8% and 41.1%, respectively.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies from Nigeria that has compared PLWHIV on ART and ART naive found a higher prevalence of MetS among the former (Muhammad et al, 2017;Muhammad et al, 2013;Ojong et al, 2022). Also, studies from other African countries (Bune et al, 2020 andOsoti et al, 2018) reported similar trend. However, among the PWoH in this study who are apparently healthy individuals, the prevalence of MetS was found to be 14.5%, which was higher than other studies (Raimi et al, 2018;Muazu et al, 2019;Ojong et al, 2022), which reported prevalence of 4.9%, 8.8% and 2.7%, respectively, though Adeyemi et al, 2017 andAmaewhule et al (2021) reported a very high prevalence of 36.8% and 41.1%, respectively.…”
Section: Discussionsupporting
confidence: 55%
“…Prevalent MetS is also directly associated with stress 151 ; elevated intraocular pressure among people without glaucoma 152 ; sensorineural hearing loss among people with Turner syndrome 153 ; exposure to pesticides 154 ; exposure to antiretroviral therapy among adults living with HIV 155 ; elevated urine sodium 156 ; poor sleep characteristics 157 ; OSA 158 ; snoring 159 ; microalbuminuria 160 ; sarcopenia in middle-aged and older nonobese adults 161 ; visceral fat level 162 ; hypoactive sexual desire disorder among postmenopausal women 163 ; high heavy metal exposure 164 ; and high occupational noise exposure. 165…”
Section: Risk Factorsmentioning
confidence: 99%